1973
DOI: 10.1145/355609.362337
|View full text |Cite
|
Sign up to set email alerts
|

On the capabilities of while, repeat, and exit statements

Abstract: A well-formed program is defined as a program in which loops and if statements are properly nested and can be entered only at their beginning. A corresponding definition is given for a well-formed flowchart. It is shown that a program is well formed if and only if it can be written with if, repeat, and multi-level exit statements for sequence control. It is also shown that if, while, and repeat statements with single-level exit do not suffice. It is also shown that any flowchart can be converted to a well-form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

1977
1977
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(41 citation statements)
references
References 3 publications
0
39
0
2
Order By: Relevance
“…Mais elles affectent la lisibilité, et aussi la facilité de preuve. Elles ont été utilisées sous le nom de « node splitting techniques » dans les recherches sur l'élimination des instructions de branchement (Manna-Ashcroft [1], Floyd-Knuth [10], PetersonKasami [20], Kosaraju [16]). Certaines de ces transformations sont mentionnées comme « évidentes » à propos des manipulations à faire sur des programmes lors de leur création (Gerhardt [12], Knuth [15]).…”
Section: Les Transformations Syntaxiquesunclassified
“…Mais elles affectent la lisibilité, et aussi la facilité de preuve. Elles ont été utilisées sous le nom de « node splitting techniques » dans les recherches sur l'élimination des instructions de branchement (Manna-Ashcroft [1], Floyd-Knuth [10], PetersonKasami [20], Kosaraju [16]). Certaines de ces transformations sont mentionnées comme « évidentes » à propos des manipulations à faire sur des programmes lors de leur création (Gerhardt [12], Knuth [15]).…”
Section: Les Transformations Syntaxiquesunclassified
“…Les structures de contrôle usuelles que sont les boucles WHILE, REPEAT ou DOFOREVER [22] ne sont que des cas particuliers de celles d'EXEL : tout programme écrit avec ces structures-ci peut être traduit trivialement en EXEL. Toutefois diverses^ questions sont encore ouvertes : si l'on ne peut traduire tout programme EXEL avec des boucles usuelles [3,11], peut-on caractériser syntaxiquement une classe de programme EXEL traduisibles?…”
Section: Equivalence Des Structures De Contrôleunclassified
“…The literature on looping constructs in programming languages is replete with results on operations with single entry points and multiple exits. Here we limit ourselves to mentioning the references [9,10,22]. In particular, Peterson et al defined in [22] a well formed program to be one in which all control structures have a single entry point, and showed that such a program need only use IF THEN, DO FOREVER, and multi level loop EXIT statements as control structures.…”
Section: Introductionmentioning
confidence: 99%